2013
DOI: 10.3389/fendo.2013.00164
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Traditional Model of the Metabolic Syndrome: The Adaptive Significance of Insulin Resistance in Fasting-Adapted Seals

Abstract: Insulin resistance in modern society is perceived as a pathological consequence of excess energy consumption and reduced physical activity. Its presence in relation to the development of cardiovascular risk factors has been termed the metabolic syndrome, which produces increased mortality and morbidity and which is rapidly increasing in human populations. Ironically, insulin resistance likely evolved to assist animals during food shortages by increasing the availability of endogenous lipid for catabolism while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 75 publications
2
41
0
Order By: Relevance
“…Consistent with the findings by others (Tsatsoulis et al 2013; Houser et al 2013; Viscarra et al 2013; Viscarra et al 2012; Friedrich 2012) we observed an increase in baseline plasma free medium- (caprate and myristate) and long-chain (oleate, vaccinate, linoleate, EPA, and palmitate) fatty acids in late-fasted seals indicating that lipolysis increased, likely as a consequence of the increased demand for energy derived from the oxidation of FFA. Our findings are corroborated by previous data demonstrating that adipose lipases (LPL and ATGL) involved in regulation of non-esterified fatty acids (NEFA) are elevated with fasting in elephant seal pups (Viscarra et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings by others (Tsatsoulis et al 2013; Houser et al 2013; Viscarra et al 2013; Viscarra et al 2012; Friedrich 2012) we observed an increase in baseline plasma free medium- (caprate and myristate) and long-chain (oleate, vaccinate, linoleate, EPA, and palmitate) fatty acids in late-fasted seals indicating that lipolysis increased, likely as a consequence of the increased demand for energy derived from the oxidation of FFA. Our findings are corroborated by previous data demonstrating that adipose lipases (LPL and ATGL) involved in regulation of non-esterified fatty acids (NEFA) are elevated with fasting in elephant seal pups (Viscarra et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…However, the highly variable relative differences in respiratory flux between seals and humans highlights the importance of considering substrate utilization and multiple respiratory states when evaluating adaptive changes in muscle aerobic capacity. Previous studies indicate that diving mammals rely almost exclusively on lipid metabolism for muscle ATP production (Davis, 1983;Davis et al, 1991;Davis et al, 1993;Kanatous et al, 2008;Trumble et al, 2010;Trumble and Kanatous, 2012;Houser et al, 2013;Crocker et al, 2014). Consequently, it was not surprising that compared with humans, adult NES mitochondria exhibited a greater capacity to oxidize lipid versus carbohydrate substrates (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Fig. 3C), and the known reliance of NESs on lipids for energy production (Houser et al, 2013;Crocker et al, 2014), activation of UCPs or the ANT by fatty acids might be expected to drive respiratory leak in the juvenile and adult seals. However, LEAK in presence of PalM was not increased with ontogeny; rather, it decreased relative to OXPHOS capacities, resulting in higher indices of fatty acid OXPHOS coupling in mature seals compared with pups and humans.…”
Section: Research Articlementioning
confidence: 99%
“…Modification to the hormonal regulation of glucose metabolism is likely an adaptive mechanism in NES Houser et al, 2013) and linked with facilitating lipid metabolism. A low level of insulin secretion facilitates lipolysis, and insulin resistance promotes lipid oxidation and restricts glucose uptake to glucose-dependent tissues, such as the central nervous system.…”
Section: Coordinated Substrate Metabolismmentioning
confidence: 99%